ANALISIS PROSEDUR PELAYANAN PERIZINAN USAHA DI BADAN PENANAMAN MODAL DAERAH DAN PELAYANAN TERPADU SATU PINTU (BPMD-PTSP) KOTA PAYAKUMBUH - Petrian, Aldi; ", Zulkarnaini, (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Analysis procedure penaman Agency regional capital and one stop (BPMD-PTSP) Payakumbuh aims to identify and analyzing the procedures of business licensing document creation services in Payakumbuh. The reality of the existing procedures are still many who do not comply with the procedures that have been set. Of the phenomenon of research, the formulation of this research is how the procedure of licensing services business in agency regional investment and one stop (BPMD-PTSP) city Payakumbuh and the factors that influence the procedures of business licensing in BPMD-PTSP city Payakumbuh. This study uses the theory proposed by Moenir.This study uses descriptive analysis. The data collecting technique is observation, interview, and literature study. Key informants of this research is the Head of integrated services, Head of staffing, general Head and equipment, employees in charge of the service, and people who take care of business licensing documents.The results showed that the procedure outlined in BPMD-PTSP not run with the maximum, it is proved they were not aware of the presence of officers will be a task that will be in laksanakannya, not optimal placement of employees. And the factors that affect the business licensing service procedures in BPMD-PTSP is a lack of awareness of employees, is not optimal staffing, as well as the need to disseminate the holding of the community.Keywords: Procedures, Licensing Services